RECONSTRUCTION OF LEGAL CULTURE OF POLITICAL PARTY IN RECRUITMEN OF LEGISLATIVE MEMBERS WITH GENDER EQUALITY - Baharudin Baharudin (UNTAG Law Review, 2018)
The legal culture of political parties in the recruitment of legislativecandidates with gender law in Bandar Lampung City is based on a "legal culture" to reveal the legal culture of political parties in the recruitment of legislative candidates with gender equality. The problem: What is the legal culture of political parties in the recruitment of legislative policies that have gender justice, namely the recruitment of legislative candidates not yet gender justice. How to build an ideal community culture in recruiting legislative candidates with gender equality. This study uses the constructivism paradigm, the socio-legal research approach, which is analyzed by Struss and Corbin models. The round of this study: 1. Political parties appear in recruitment and legislative legislation has not yet been adopted in the legal culture, because it still separates women's rights. 2. The legal culture of political parties in the recruitment of legislative candidates has no gender, which is caused by the factors of political parties participating in the election that are still recruiting and in accordance with patriarchal ideology, 3. The ideal legal construction of political parties in recruiting legislative candidates with gender equality, namely recruiting legislative candidates must be fair, not separate women's political rights to be nominated or appointed aslegislative candidates in general elections, fulfill legal requirements, not only fulfill 30% representation of women, must be prepared through cadres, education and training, have become members of a political party of at least 6 months to 1 year, noble, loyal, dedicated, and loyal to Pancasila and the 1945 Constitution of the Republic of Indonesia.